A Survey of Post-War Levels of Business Activity - Eckler, A. Ross (The Review of Economics and Statistics, 1928)
BEFORE we consider the varying advances achieved by various classes of industry since I9I9, it is useful and interesting to review the broad economic aspects of the period through which we have been passing. From our study of the cyclical fluctuations during the past sixty years, we have learned that economic data for that time can not be analyzed as a homogeneous whole. We find that there are certain periods which have been characterized by cyclical swings of great amplitude and much irregularity. There are other periods in which the ups and downs of business have been moderate, but, nevertheless, well defined. This distinction is clearly apparent in the fluctuations of the rates on prime commercial paper from i866 to I9271. During the reconstruction period from i866 to I873, the far reaching after-effects of the Civil War brought about extreme fluctuations in the rates on commercial paper. After a period of relatively narrow fluctuations, there emerged between I890 and I899 another interval characterized by wider variations, when the usual cyclical movements were greatly intensified by the Sherman Silver Purchase Act, by the menace of the free silver episode, and by the outbreak of the Spanish-American War. On the other hand, there were two long intervals in the sixty years under examination when money rates were virtually free from such extreme movements. From I875 to I890 and again from I900 to I9I3, there were periods during which the economic mechanism, having outgrown the influence of the tremendous disturbing forces which immediately preceded, and not being subjected for any considerable interval to the pressure of unusual new elements, settled down to a more stable and regular type of oscillation. The outbreak of the war in I9I4, however, ushered in another period featured by wide movements. Indeed, the war years were so dominated by military demands that critical economic analysis of this period is hindered by many obstacles. It will be noted, however, that during the war ancl post-war years, money rates have not exhibited the same degree of irregular month to month fluctuation which had characterized previous comparable periods. This reflects the influence of the federal reserve system. During I9I9-27, there are new and important elements in the economic situation, for which allowance must be made before one applies the methods of analysis suitable for such a period as I903-I3. The business situation in the United States has been profoundly influenced by the march of post-war developments in Europe, which brought financial upheaval and demoralization of markets. It has become increasingly evident that the United States is not an isolated self-sufficient nation, but, on the contrary, is affected materially by international developments. The fact that our country now has the greatest accumulation of gold in modern times serves to explain certain unusual phases in postwar business conditions. Furthermore, there have been substantial changes in the standard of living in this country, as well as in buying habits. These changes in the standard of living have been of such order as to have important effects on the usefulness of indexes of prices. Available wholesale price indexes are heavily weighted with data for staple basic commodities, and fail to measure the price movements of many of those things which people want to buy. People will deprive themselves in a variety of ways so that they may have automobiles, radios, fur coats, ultra-modern apartments, and other goods of the luxury class. This, then, means that price indexes fail to register adequately the price changes for articles people most desire to buy. It would be possible to cite many additional reasons to show why the period I9I9-27 has been an unusual one, but such enumeration is unnecessary to indicate that the injection of new elements into the compound we call the business situation has necessitated a revised point of